Natural Killer T (NKT) Cells and Periodontitis: Potential Regulatory Role of NKT10 Cells - Samanta Melgar-Rodríguez; Emilio A. Cafferata; Nicolás I. Díaz; Miguel A. Peña; Luis González-Osuna; Carolina Rojas; Alfredo Sierra-Cristancho; Angélica M. Cárdenas; Jaime Díaz-Zúñiga; Rolando Vernal (Mediators of Inflammation)
Natural killer T (NKT) cells constitute a unique subset of T lymphocytes characterized by specifically interacting with antigenic glycolipids conjugated to the CD1d receptor on antigen-presenting cells. Functionally, NKT cells are capable of performing either effector or suppressor immune responses, depending on their production of proinflammatory or anti-inflammatory cytokines, respectively. Effector NKT cells are subdivided into three subsets, termed NKT1, NKT2, and NKT17, based on the cytokines they produce and their similarity to the cytokine profile produced by Th1, Th2, and Th17 lymphocytes, respectively. Recently, a new subgroup of NKT cells termed NKT10 has been described, which cooperates and interacts with other immune cells to promote immunoregulatory responses. Although the tissue-specific functions of NKT cells have not been fully elucidated, their activity has been associated with the pathogenesis of different inflammatory diseases with immunopathogenic similarities to periodontitis, including osteolytic pathologies such as rheumatoid arthritis and osteoporosis. In the present review, we revise and discuss the pathogenic characteristics of NKT cells in these diseases and their role in the pathogenesis of periodontitis; particularly, we analyze the potential regulatory role of the IL-10-producing NKT10 cells.